Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Johanna Jakobsdottir; Sven J van der Lee; Joshua C Bis; Vincent Chouraki; David Li-Kroeger; Shinya Yamamoto; Megan L Grove; Adam Naj; Maria Vronskaya; Jose L Salazar; Anita L DeStefano; Jennifer A Brody; et al. (PLoS Genetics)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.